2016
DOI: 10.1111/tops.12242
|View full text |Cite
|
Sign up to set email alerts
|

Improving With Practice: A Neural Model of Mathematical Development

Abstract: The ability to improve in speed and accuracy as a result of repeating some task is an important hallmark of intelligent biological systems. Although gradual behavioral improvements from practice have been modeled in spiking neural networks, few such models have attempted to explain cognitive development of a task as complex as addition. In this work, we model the progression from a counting-based strategy for addition to a recall-based strategy. The model consists of two networks working in parallel: a slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This pattern is compatible with inhibition deficits often associated with DD ( Wang et al, 2012 ; Szucs et al, 2013a ; Bugden and Ansari, 2015 ). As suggested by Aubin et al (2016) , individuals with DD might fail to consolidate magnitude knowledge and to produce the shift from the “slow” computing neural network to the “fast” retrieval network. Hence, they must invest more cognitive efforts in order to ignore irrelevant magnitude information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This pattern is compatible with inhibition deficits often associated with DD ( Wang et al, 2012 ; Szucs et al, 2013a ; Bugden and Ansari, 2015 ). As suggested by Aubin et al (2016) , individuals with DD might fail to consolidate magnitude knowledge and to produce the shift from the “slow” computing neural network to the “fast” retrieval network. Hence, they must invest more cognitive efforts in order to ignore irrelevant magnitude information.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive method as well as the statistical analysis of the current study enabled us not only to study the differences between automatic processing of area vs. perimeter (i.e., investigating magnitude sense in DD), but also to investigate whether DD participants indeed perform poorly or differently on continuous magnitude processing tasks in initial vs. proficiency stages of learning (i.e., to investigate learning functions in DD). Earlier studies showed that even a small number of rehearsals of numerical problems led to automatic processing and to changes in brain functions ( Ischebeck et al, 2007 ; Aubin et al, 2016 ). For instance, Ischebeck et al (2007) found that very short training (eight repetitions) in multiplication problems led to a decrease in the activity of fronto-parietal brain areas related to calculation and numerical processing ( Menon et al, 2000 ; Dehaene et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…R. Soc. B 375: 20190304 may be investigated further by instantiating a dynamic neural implementation of the model via the NEF [83], where learning algorithms employing, for instance, spike-timing-dependent plasticity can be applied to learn functions over time [116].…”
Section: (C) Hierarchical Dependenciesmentioning
confidence: 99%